1973
DOI: 10.1073/pnas.70.2.390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stimulation of the Host Defense System by Coenzyme Q 10 on Dibenzpyrene-Induced Tumors and Infection with Friend Leukemia Virus in Mice

Abstract: Members of the coenzyme Q group increase the phagocytic activity in rats, as measured by the carbon clearance technique, and increase the hemolytic antibody formation in mice. In addition, prior treatment with low doses of chloroquine hydrochloride combined (ii) Treatment with coenzyme Qio reduced the percentage of mice with tumors, increased the number of survivors, and reduced the tumor size in mice with tumors induced by 3,4,9,10-dibenzpyrene. The effect on both tumor systems was dose-dependent. These studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In addition, CoQ 10 is a rate-limiting component of the mitochondrial electron transport system leading to ATP production which is essential for eukaryotic cell survival and energy requiring processes, including proliferation, apoptosis, angiogenesis, and immune function [5-8]. Epidemiological evidence, while limited, suggests inverse associations of tocopherols and CoQ 10 with the risk of certain cancers [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CoQ 10 is a rate-limiting component of the mitochondrial electron transport system leading to ATP production which is essential for eukaryotic cell survival and energy requiring processes, including proliferation, apoptosis, angiogenesis, and immune function [5-8]. Epidemiological evidence, while limited, suggests inverse associations of tocopherols and CoQ 10 with the risk of certain cancers [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…All mammalian cells are capable of synthesizing CoQ 10 (or closely related molecules) in a complex biosynthetic pathway involving the mevalonate pathway (also responsible for cholesterol and dolichol synthesis) and tyrosine, in a process dependent upon eight essential vitamins and nutrients (3,4). Mitochondrial energy production is essential for eukaryotic cell survival and CoQ 10 is a key molecule in all energy requiring processes, including proliferation, apoptosis, angiogenesis, and immune function (58), suggesting the potential for multiple roles in the initiation and progression of cancer. Despite the critical role of CoQ 10 in many cellular functions, its potential relationship with cancer development and progression has not received appropriate attention.…”
Section: Introductionmentioning
confidence: 99%
“…49 A study by Bliznakov illustrated that injected doses of CoQ 10 (150-750 µg) in mice significantly delayed the onset of 3,4,9,10-dibenzpyrene-induced tumor formation, decreased tumor size, and reduced mortality rates compared with mice that were not given a supplemental injection. 50 A more recent trial showed similar results in male Sprague-Dawley rats, where CoQ 10 supplementation (0.4 mg/kg/day) demonstrated therapeutic potential against trichloroacetic acid-induced hepatocellular carcinoma, mediated by the suppression of lipid peroxidation, the prevention of reduced glutathione depletion, and decreased elevations of tumor necrosis factor-α and nitric oxide in liver tissue. 51 CoQ 10 use with chemotherapy was shown to be effective in patients suffering from breast cancer.…”
Section: Cancermentioning
confidence: 50%